Nne (Things We Lost in the Fire, 2020)
BACKGROUND: Nursing interns (fourth-year undergraduate nursing students in their clinical practicum) often report low career intention, closely linked to transition shock during role transition. PURPOSE: To examine how transition shock affects career intention and the moderating role of professional identity using ecological momentary assessment. METHODS: The study tracked 1162 nested observations of 83 nursing interns over 14 days. Data were analyzed using a 2-level Hierarchical Linear Modeling. RESULTS: Transition shock was relatively high (69.22 ± 25.17) and varied significantly (P < .01), while career intention remained moderate and stable (2.42 ± 0.82). Sociocultural and development shock negatively predicted career intention (β = .02, P < .01). Professional identity showed a direct protective effect (β = -.01, P < .01) but no moderating role. CONCLUSIONS: Nursing interns show fluctuating shock but stable career intention. Sociocultural challenges lower intention, while professional identity buffers it. Strengthening professional identity mitigates shock, and better adaptation supports internship success.